A new method for analysis of dual pore size distributions in shale using nitrogen adsorption measurements. (15th December 2017) - Liu, Jianwu; Li, Peichao; Sun, Ziyu; Lu, Zhiwei; Du, Zonghe; Liang, Haibo; Lu, Detang
Abstract: A new method is proposed to distinguish between cylindrical pores and slit pores of porous materials and obtain their individual pore size distributions (PSDs). The proposed method is based on nitrogen adsorption isotherms at 77.3 K. First, we develop the conventional methods by utilizing both adsorption and desorption branches of the isotherms and deriving the volume distribution of the two types of pores. The method formulation and implementing procedure is given in detail. Then the isotherms of SBA-15 sample are used to verify the proposed method in the case of single-pore-type. Finally, the proposed method is applied to analyze the pore structure characterization of shale sample. The results depict that both the adsorbed quantity and pore volume are separated into two distinct parts contributed by cylindrical pores and slit pores respectively. That's to say, the proposed method can distinguish clearly between the two types of pores. This study can provide us a better understanding of the complicated pore structure of shale. Furthermore, it may have implications for shale gas production.